SOIL SEED BANK OF AN EXOTIC Acacia sp. PLANTATION AND AN ADJACENT TROPICAL HEATH FOREST IN BRUNEI DARUSSALAM - Adrian Lee Rahman Suhaili; Kushan Tennakoon; Rahayu Sukmaria Sukri (SEAMEO BIOTROP, 2015)
Acacias are among the most successful invasive plants in tropical regions, causing significant negative impacts on biodiversity and ecosystem services of invaded habitats. Their invasiveness is partly attributed to their ability to accumulate large soil seed banks in areas they colonize. This study compared seedling emergence and soil seed bank composition under an Acacia mangium plantation and an adjacent tropical heath (kerangas) forest in the Andulau Forest Reserve, Brunei Darussalam. Soil samples were collected from ten 20 × 20 m plots established in three contrasting habitats: the plantation, the adjacent heath forest, and the transition zone between them. Soil samples were subjected to smoke and heat treatments, and seedling emergence was monitored daily over a 12-week period. In a parallel assessment, variations in species richness, seed density, and seed viability were examined across the ten plots. Seedling emergence was highest in the plantation and lowest in the heath forest plots. However, no significant differences among treatments and no significant treatment–habitat interactions were detected. Species richness, seed density, and seed viability in the plantation plots were significantly lower than those in the transition zone and intact heath forest plots. Acacia mangium seeds were not detected in the heath forest soil seed banks but were found in plantation and transition zone plots. The lower native plant species richness, seed density, and viability in the plantation may indicate a higher regeneration potential for the heath forest habitat should major disturbance occur within the reserve. Proper plantation management and continuous monitoring of soil seed banks are recommended to minimize the spread of invasive Acacia species into tropical heath forests of Borneo.